SCREEN HOUSE ASSESSMENT OF NEEM-FORTIFIED CASSAVA PEEL POWDER FOR CONTROLLING NEMATODES AND YIELD IMPROVEMENT OF SUGARCANE (SACCHARUM OFFICINARUM) - SLOMON, S.; AFOLAMI, S. O.; S. ODEYEMI, T. O. S. POPOOLA, J. J. ATUNGWU,; DARAMOLA, F. Y. (International Multidisciplinary Research Journal, 2018)
Screen house trials for the assessment of Neem-fortified cassava peels for control of plant-parasitic nematodes and yield improvement of sugarcane (Saccharum officinarum) were conducted in Moor plantation, Ibadan, Southwest Nigeria. Cassava peel powder (CPP) solely and in combination with Neem Leaf Powder (NLP) or Neem Seed Powder (NSD) at 100gCPP/10 Litre soil, 90gCPP+30gNSP/10 Litre soil, 80gCPP+20gNSP/10 Litre soil, 70gCPP+30gNSP/10 Litre of soil, 90gCPP+10gNLP/10 Litre soil, 80gCPP+20gNLP/10 Litre soil, 70gCPP+30gNLP/10 Litre soil were incorporated into potted naturally infested soil in the screen house, at 14 d before planting. All treatments significantly (p<0.05) reduced plant-parasitic nematode population. Soil treatment with Cassava Peel Powder in combination with Neem Leaf Powder at 70gCPP+30gNLP/10 Litre of soil recorded the most effective control for soil and root nematodes associated with sugarcane in the two screen house trials. The soil amendment also supported the good vegetative growth and yield of sugarcane, which is an indication of its capability to improve soil fertility.